Measures According to Buddhist Philosophy to Prevent Corruption and Misconduct: Measures According to Buddhist Philosophy to Prevent Corruption and Misconduct - Sesmapol, Thaworn; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research are: to present patterns and types of corruption and misconduct: Administrative corruption, Economic corruption and Political corruption To present measures to preventing corruption and misconduct: Political Control, Administrative Control, Public Control and Functional Control to present measures according and to Buddhist philosophy to prevent corruption and misconduct : three benefit, foundation, five principles, three good faith, Hiriotappa, detached, right livelihood and four virtues for a good household life.